Chronic lameness caused by vascular compression of the iliac artery and vein by a malignant melanoma in the pelvis of a grey Spanish gelding. (20th June 2019) - Van Ongeval, A.; van de Velde, N.; Raes, E.; Oosterlinck, M.
Summary: An 11‐year‐old grey Spanish gelding was presented with chronic lameness of the right hindlimb, with abduction of the limb during the swing phase. Based on a comprehensive lameness examination, the problem was localised to the pelvic region. Rectal and ultrasonographic examinations revealed a mass in the pelvic region in close association with the iliac artery and vein, and ultrasonographic indications of vascular compression. Considering the clinical presentation of a grey middle‐aged horse with multifocal melanoma‐like nodules at the level of the perineum, tail base, preputium and penis, a malignant melanoma with secondary vascular or neurological compression was suspected. Post‐mortem and histological examination confirmed the diagnosis of malignant melanoma with vascular compression of the iliac artery and vein and infiltrative growth in the iliac vein.